SWOT Analysis of the Effect of New Materials on Engine Performance and Durability - Risdianto, Anauta Lungiding Angga; Saputra, Rahmad Surya Hadi; Thohirin, Muh; Chin, Jacky (Journal of Renewable Engineering, 2025)
Material innovation in the manufacturing and automotive industries plays an important role in improving engine performance and durability. Conventional materials such as steel and aluminum have limitations in resistance to extreme temperatures and wear, so new materials such as high-performance metal alloys, carbon fiber composites, and nanotechnology-based materials are developed as solutions. These materials are capable of improving energy efficiency, reducing weight, and extending component life. However, the adoption of new materials faces challenges such as high production costs, fabrication complexity, and validation in real operational environments. Therefore, collaboration between academia, industry and government is needed to develop solutions that are not only technically superior, but also economical and sustainable. This research uses the SWOT method to analyze the strengths, weaknesses, opportunities, and threats in the application of new materials. Data were obtained through literature studies, laboratory experiments, and expert interviews. The analysis results show that materials such as carbon fiber composites (CFRP) have advantages in fuel efficiency and corrosion resistance, but also face challenges in production and maintenance costs. With innovations in manufacturing technology and a more sustainable approach, new materials have the potential to be the optimal solution for the automotive and manufacturing industries in the future